Effect of Temperature on the Performance of Polymer Electrolyte Membrane Water Electrolysis: Numerical Analysis of Electrolysis Voltage Considering Gas/Liquid Two-Phase Flow. Issue 4 (1st January 2019) - Kai, Jyunya; Saito, Ryo; Terabaru, Kenji; Li, Hua; Nakajima, Hironori; Ito, Kohei
Abstract : The numerical analysis conducted in this study proposes a guideline to maximize the high-temperature effect, which is expected to reduce the electrolysis voltage of the polymer electrolyte membrane water electrolyzer. High-temperature operation is intuitively thought to reduce activation overvoltages. However, a further consideration predicts that high temperature, especially a temperature higher than the saturated temperature regulated in the operation pressure, decreases the liquid saturation and causes shortage of water, leading to a large increase in overvoltages. This high temperature problem is analyzed using the developed theoretical model, which considers gas/liquid behavior. The analysis suggests that, if the gas saturation in the anode catalyst layer is kept at or below 0.3 by increasing the pressure, liquid water in the catalyst layer is sufficient to OER catalytic ability regulated by exchange current density, demonstrating that the high-temperature effect works. According to this guideline, increasing the temperature with pressurization can monotonically reduce the anode activation overvoltage. For instance, raising the temperature from 100 to 120°C and raising the pressure from 0.13 to 0.22 MPa can prevent the gas saturation from increasing beyond 0.3 and allows the lower electrolysis voltage to vary from 1.57 to 1.51 V.